Estimating Symbiont Abundances and Gill Surface Areas in Specimens of the Hydrothermal Vent Mussel Bathymodiolus puteoserpentis Maintained in Pressure Vessels - Duperron, Sébastien; Quiles, Adrien; Szafranski, Kamil M.; Léger, Nelly; Shillito, Bruce (Frontiers in Marine Science, 2016)
The hydrothermal vent mussel Bathymodiolus puteoserpentis hosts gill-associated sulfur- and methane-oxidizing bacteria which sustain host nutrition and allow it to reach high densities at various sites along the northern Mid-Atlantic Ridge. Previous studies have demonstrated that in similar dual symbioses, relative abundances of each bacterial type could change following variations in symbiont substrate availabilities. In this study, pressurized recovery and incubations in pressure vessels were used to test whether B. puteoserpentis symbionts displayed similar behavior in the presence of symbiont substrates. The relative abundances of both types of symbionts were analyzed using fluorescence in situ hybridization (FISH) and group-specific gene copy numbers were assessed using qPCR. Specimens sampled using isobaric and non-isobaric recovery contained similar relative proportions (in surface coverage) of sulfur- and methane-oxidizing bacteria indicating that recovery type did not have impact on measured relative areas. Similarly, pressurized incubations with different substrates did lead to significant differences in the relative surface coverage of the two types of bacteria, although slight variations were measured with qPCR, suggesting changes in relative abundances of gene copy numbers but not in relative areas covered. Total gill surface areas and total bacterial numbers in specimens were estimated for the first time. Symbiont bearing-mussels display exchange surfaces about 20-fold higher than those found in similar-sized coastal mussels, and mean bacterial numbers of 2.5*1012 per specimen were estimated. This emphasizes that symbiotic mussels are a major reservoir of bacteria in vent ecosystems.